National Eye Service (1929)
1929 1929 1920s 12 pages NATIONAL EYE SERVICE [2] 4. Those who have disorders of the nervous system affecting the sight. 5. Those who have constitutional disease affecting sight (diseases of the kidneys, blood-vessels, etc., diabetes and various kinds of poisoning). 6. Those who have serious disease of the eyes affecting sight. 7. Those whose headaches or suspected eye-defects have nothing to do with the eyes at all. It has been estimated that in over forty per cent of all cases of imperfect sight the cause is [due] to other than purely ocular defects. The great majority of these cases, if correctly diagnosed and treated in time by a doctor, can be cured. It is therefore most important to obtain medical advice immediately the sight becomes troublesome. What the service is and to whom it is available Realising the supreme importance of proper attention to the eyes, the British Medical Association has organised an ophthalmic medical service for the testing of vision and examination of the eyes by specially qualified medical practitioners. The services of these eye specialists have previously been available only in the hospitals or by private consultation at the usual specialists' fees. 292/841.4/1/61